Nymphal Stages of Abrocomophaga hellenthali (Phthiraptera, Gyropidae), a parasite of Octodon degus (Rodentia, Octodontidae) - Armando C. Cicchino; Dolores del Carmen Castro (Iheringia: Série Zoologia, 2002)
The three nymphal instars of Abrocomophaga hellenthali Price & Timm, 2000 are described and compared with both sexes of the adult stage. The most remarkable quali and quantitative body features of all instars are cathegorized and its progression along the development stated.